FRAME IN ARTICLES ATTENDED BY "CAMEL" LMG - Jumayeva Marjona Erkinovna (American Journals, 2024)
This article analyzes frames and slots studied as a basic concept in cognitive linguistics based on articles attended by the Camel Dictionary Group. The article used comparison and browsing methods.
Keywords: Zoonym, concept, frame, slot, cognitive linguistics, cognition, totem.